Real-world efficacy and safety of vedolizumab in managing ulcerative colitis versus Crohn's disease: results from an Italian multicenter study. (4th March 2023) - Mocci, Giammarco; Tursi, Antonio; Maconi, Giovanni; Cataletti, Giovanni; Mantia, Beatrice; Serio, Mariaelena; Scarcelli, Antonella; Pagnini, Cristiano; Graziani, Maria Giovanna; Di Paolo, Maria Carla; Pranzo, Giuseppe; Luppino, Ileana; et al.
ABSTRACT: Background: Vedolizumab (VDZ) can be used to treat refractory ulcerative colitis (UC) and Crohn's disease (CD). We assessed whether there are differences in treating UC vs CD with VDZ. Research design and methods:  Mayo score in UC and the Harvey-Bradshaw Index (HBI) in CD scored the clinical activity. Achievement and maintenance of clinical remission during the follow-up, and safety were the primary endpoints. Results: 729 patients (475 with UC and 254 with CD), median follow-up of 18 (IQR 6-36) months, were enrolled. Clinical remission at the 6 th month of treatment was achieved in 488 (66.9%) patients (74.4% in CD vs 62.9% in UC, p<0.002) while, during the follow-up, no difference was found (81.5% in the UC group and 81.5% pts in the CD group; p=0.537). The clinical remission at the 6 th month of treatment (p=0.001) and being naïve to biologics (p<0.0001) were significantly associated with prolonged clinical remission. The clinical response was significantly higher in UC (90.1%) vs CD (84.3%) (p=0.023), and surgery occurred more frequently in CD (1.9% in UC vs 5.1% in CD, p=0.016). Conclusion: We found differences when using VDZ in UC vs CD in real life. These parameters can help the physician predict this drug's longterm efficacy.